Strong-acid-resistant environment-friendly coating material for building as well as preparation method and application thereof

Through the design of inorganic composite coating materials, the combination of solid and liquid phase raw materials has been used to solve the problems of poor environmental protection and easy aging of existing acid-resistant coating materials, and the efficient acid resistance and long life are achieved, and the preparation process is simplified. Acid resistance protection in buildings.

CN119307158APending Publication Date: 2025-01-14KUNMING UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411669718.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing acid-resistant coating materials contain a large amount of volatile organic compounds, which endanger human health and are difficult to meet environmental protection standards. The coating materials are prone to aging, have a short life, are complex in preparation process, and have a single scope of application.

Method used

Use solid phase raw materials such as silica, kaolin, anhydrous calcium sulfate, aluminum tripolyphosphate, tantalum oxide, yttria stable zirconia, boron oxide, calcium carbonate and liquid phase raw materials water glass, adhesive, curing agent, disinfection The inorganic composite coating composed of foaming agent is prepared by wet grinding and magnetic stirring, sprayed or brushed on the surface of building materials, and cured at room temperature.

Benefits of technology

It achieves good acid resistance and long life of inorganic coatings, reduces the amount of organic matter, avoids volatility and aging problems, simplifies the preparation process, and is suitable for acid resistance protection of buildings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307158A_ABST
    Figure CN119307158A_ABST
Patent Text Reader

Abstract

The invention discloses a strong-acid-resistant environment-friendly coating material for buildings as well as a preparation method and application of the strong-acid-resistant environment-friendly coating material. The coating material consists of the following raw materials in parts by weight: 5-20 parts of water glass, 5-10 parts of silicon dioxide, 5-10 parts of kaolin, 20-40 parts of anhydrous calcium sulfate, 20-40 parts of aluminum triphosphate, 1-5 parts of tantalum oxide, 1-5 parts of yttria-stabilized zirconia, 1-5 parts of boric oxide, 1-5 parts of zinc oxide, 1-5 parts of calcium carbonate, 20-40 parts of an adhesive, 2-8 parts of a curing agent and 1-2 parts of a defoaming agent. The preparation method comprises the following steps: mixing the solid-phase raw materials in proportion, carrying out ball milling for 60-720 minutes at the ball milling speed of 100-800 r / min by taking alcohol and water as wet milling liquid, taking out, drying for 36-48 hours, sieving with a 200-mesh sieve to obtain solid-phase powder, putting the solid-phase powder into a beaker, mixing with the water glass, slowly adding a mixture of the adhesive, the curing agent and the defoaming agent, and magnetically stirring to obtain the acid-resistant coating paint for the building. The coating disclosed by the invention is simple in preparation method, remarkable in long-acting protection effect in an acid environment and suitable for popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite material coatings, and in particular relates to a strong acid-resistant environmentally friendly coating material for construction, and a preparation method and application thereof. Background Art

[0002] In industrial plants and chemical storage warehouses that use strong acids as production raw materials or produce strong acids, strong acids will cause hydrogen corrosion with many building materials, especially steel structures. When building materials are exposed to strong acid environments for a long time or chemical raw materials leak, there is a phenomenon of corrosion of building materials. Therefore, related working environments (such as industrial plants and chemical storage warehouses) require acid-resistant anti-corrosion coatings to protect building walls and steel structures to prevent erosion by special industrial environments and thus affect building safety.

[0003] Anticorrosive coatings are applied to the surface of materials to form a continuous coating that adheres firmly, isolating the materials from the surrounding media (such as moisture, water, chemical atmosphere, electrolyte, organic solvent, acid, alkali, etc.), thus eliminating and alleviating the chemical and electrochemical effects with the surrounding media. Existing acid-resistant coating materials have the following main problems: they contain a large amount of volatile organic matter, which releases toxic and harmful substances into the air, endangering human health and making it difficult to meet environmental protection standards; the coating raw materials are basically completely organic, which is easy to age, has a short lifespan and is difficult to serve for a long time; the preparation process is relatively complicated and the scope of application is generally single, etc. The specific problems are as follows: Most of the acid-resistant coating materials on the market contain non-environmentally friendly ingredients. However, my country's environmental awareness is gradually increasing, and the development of environmentally friendly coatings has become a major trend in the coatings industry. Traditional solvent-based coatings contain a large amount of volatile organic compounds (VOCs). During the production and use process, these organic solvents will evaporate into the atmosphere, causing air pollution and harming human health. Low-VOC coatings have become a hot topic for scientific researchers.

[0004] The existing alkali-resistant coating raw materials are basically entirely organic. During long-term use, they face serious aging problems, and the protective effect gradually decreases, causing the coating to bubble, crack, and even fall off, causing the coating to lose its protective function, thus leading to material failure and greatly reducing its actual service life.

[0005] Since inorganic materials have the advantages of good chemical stability, strong acid resistance and easy availability of raw materials, new inorganic composite coatings have replaced traditional organic acid-resistant coating materials, achieving the characteristics of long life and strong acid resistance, making more contributions to environmental protection and sustainability.

[0006] The invention aims to provide a strong acid resistant and environmentally friendly coating material for construction. Summary of the invention

[0007] The first purpose of the present invention is to provide a strong acid resistant and environmentally friendly coating material for construction, and the second purpose of the present invention is to provide a preparation method and application of the coating material.

[0008] The first object of the present invention is achieved in this way: an acid-resistant coating for construction, which is composed of solid raw materials and liquid raw materials, wherein the solid raw materials are silicon dioxide, kaolin, anhydrous calcium sulfate, aluminum tripolyphosphate, tantalum oxide, yttria-stabilized zirconium oxide, boron oxide, and calcium carbonate; and the liquid raw materials are water glass, an adhesive, a curing agent, and a defoaming agent; The content of each raw material component is as follows: 5-20 parts of water glass, 5-10 parts of silicon dioxide, 5-10 parts of kaolin, 20-40 parts of anhydrous calcium sulfate, 20-40 parts of aluminum tripolyphosphate, 1-5 parts of tantalum oxide, 1-5 parts of yttria-stabilized zirconium oxide, 1-5 parts of boron oxide, 1-5 parts of zinc oxide, 1-5 parts of calcium carbonate, 20-40 parts of binder, 2-8 parts of curing agent, and 1-2 parts of defoaming agent.

[0009] The second object of the present invention is achieved in this way. The preparation method of the acid-resistant coating for construction is as follows: the solid raw materials are mixed in proportion, ball-milled for 60-720 minutes with alcohol and water as wet grinding liquids, the ball-milling rate is 100-800r / min, and then taken out and dried for 36-48 hours, and passed through a 200-mesh sieve to obtain a solid phase powder, which is mixed with water glass in a beaker, and then a mixture of an adhesive, a curing agent and a defoaming agent is slowly added and magnetically stirred to obtain the acid-resistant coating for construction.

[0010] The application of the acid-resistant coating for construction is in the preparation of a coating on the surface of a building. The specific coating method is to polish and clean the surface of a building material, and then evenly coat it on the surface of the building material by spraying or brushing, with a coating thickness of 0.5 to 10 mm.

[0011] The beneficial effects of the present invention are: 1. More than 90% of phosphogypsum is CaSO4·2H2O. The application of anhydrous calcium sulfate in the present invention can provide a solution for the accumulation of phosphogypsum and can effectively use a huge amount of phosphogypsum. According to the actual application situation, the present invention mixes a variety of inorganic materials in a certain proportion, takes anhydrous calcium sulfate as the main raw material, and only adds a small amount of organic matter. Anhydrous calcium sulfate and epoxy resin have good acid resistance, and have good acid resistance after blending. It is immersed in a 65% concentration nitric acid solution for 7-15 days with basically no weight loss, and can achieve long-term protection in this acidic environment; and it has good mechanical properties. After the coating is prepared and applied to the surface of building materials (steel structural parts, building walls and cement walls), it can reach the use conditions by natural curing at room temperature for 24~48h; 2. The present invention adopts inorganic solid phase powder and organic epoxy resin to prepare a strong acid resistant environmentally friendly coating, thereby reducing the amount of organic matter used, avoiding the volatilization of organic matter, and at the same time largely avoiding the aging problem caused by organic matter.

[0012] 3. The preparation method of the present invention is simple and suitable for popularization and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is an acid-resistant test diagram of the acid-resistant coating material prepared in Example 1; Figure 2 The acid-resistant test weight change curve of the acid-resistant coating material prepared in Example 1; Figure 3 This is a sample picture of the acid-resistant coating material prepared in Example 1 after the acid-resistant test was carried out for fifteen days; Figure 4 This is a graph of the mechanical properties of the nanoindentation Young's modulus of the acid-resistant coating material prepared in Example 1; Figure 5 This is a graph of the tensile strength of the acid-resistant coating material prepared in Example 1. DETAILED DESCRIPTION

[0014] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0015] The invention discloses an acid-resistant coating for building, which is composed of solid raw materials and liquid raw materials. The solid raw materials are silicon dioxide, kaolin, anhydrous calcium sulfate, aluminum tripolyphosphate, tantalum oxide, yttria-stabilized zirconium oxide, boron oxide, and calcium carbonate; and the liquid raw materials are water glass, an adhesive, a curing agent, and a defoaming agent. The content of each raw material component is as follows: 5-20 parts of water glass, 5-10 parts of silicon dioxide, 5-10 parts of kaolin, 20-40 parts of anhydrous calcium sulfate, 20-40 parts of aluminum tripolyphosphate, 1-5 parts of tantalum oxide, 1-5 parts of yttria-stabilized zirconium oxide, 1-5 parts of boron oxide, 1-5 parts of zinc oxide, 1-5 parts of calcium carbonate, 20-40 parts of binder, 2-8 parts of curing agent, and 1-2 parts of defoaming agent.

[0016] The modulus of the water glass is 2.6-3.7, and the particle sizes of the silicon dioxide, kaolin, anhydrous calcium sulfate, aluminum tripolyphosphate, tantalum oxide, yttria-stabilized zirconium oxide, boron oxide, zinc oxide, and calcium carbonate are 250-500 meshes.

[0017] The adhesive is epoxy resin, phenolic resin and 0.1-20% polyvinyl alcohol.

[0018] The curing agent is phthalic anhydride, 4 , 4-Diaminodiphenylmethane or 0.1~5% ethylenediamine.

[0019] The defoamer is polydimethylsiloxane or 0.05-1% of a polyether defoamer.

[0020] The present invention also provides a preparation method of the acid-resistant coating for construction, which comprises mixing various solid raw materials in proportion, ball-milling for 60-720 minutes with alcohol and water as wet-milling liquids, at a ball-milling rate of 100-800 r / min, drying for 36-48 hours after taking out, passing through a 200-mesh sieve to obtain solid phase powder, mixing it with water glass in a beaker, and then slowly adding a mixture of an adhesive, a curing agent and a defoaming agent to obtain the acid-resistant coating for construction through magnetic stirring.

[0021] The magnetic stirring time is 20~400min, and the stirring speed is 100~700r / min.

[0022] The present invention further provides the use of the acid-resistant coating for construction in preparing a coating on a building surface. The specific coating method is to polish and clean the surface of a building material, and then evenly coat the surface of the building material by spraying or brushing, with a coating thickness of 0.5 to 10 mm.

[0023] Spraying mainly involves connecting a spray pot to an air compressor and relying on strong air pressure to spray the coating onto the steel substrate. The spraying rate of the spray pot is 0.3~6L / min, and the spraying distance from the metal is 10cm~80cm.

[0024] The building surface material is steel structural parts, building walls or cement walls.

[0025] Example 1 5g of silicon dioxide, 5g of kaolin, 20g of anhydrous calcium sulfate, 20g of aluminum tripolyphosphate, 3g of tantalum oxide, 2g yttria-stabilized zirconium oxide, 2g boron oxide, 2g zinc oxide, and 2g calcium carbonate were mixed, and ball-milled for 360min with alcohol and water as wet-milling liquids at a ball-milling rate of 400r / min. After being taken out, the mixture was dried for 48h, and a solid phase powder was obtained after being sieved through a 200-mesh sieve. After being mixed with 8g water glass in a beaker, 30g epoxy resin, 8g phthalic anhydride, and 1.5g polydimethylsiloxane were slowly added, and stirring was continued until fully fused to obtain an acid-resistant coating material. After testing, the Young's modulus of the acid-resistant coating material prepared in Example 1 was 1.2-6.5GPa ( Figure 4 ).

[0026] The coating prepared in Example 1 was subjected to a tensile test, and it was found that it reached a maximum tensile strength of 40.85 MPa at a strain of 7.70%, indicating that it has good mechanical properties and can ensure the bonding strength of the coating material during service, the mechanical properties of the coating, etc. ( Figure 5 ).

[0027] After cleaning the surface of building materials (such as steel structures, building walls and cement walls), Use a high-pressure air gun to blow away surface impurities. Connect the spray pot to a vacuum pump and spray the anti-oxidation coating evenly on the surface of the building material. The spray rate of the spray pot is 1 L / min, the spray distance between the spray pot and the metal is 20 cm, and the coating thickness is 1 mm. After curing at room temperature for 36 hours, the acid-resistant coating is obtained.

[0028] The spraying of acid-resistant coating material is changed to brushing. The specific method is: use a brush to dip the acid-resistant and fire-resistant coating on the surface of the building material and apply it. After brushing, use the brush again to repair the unbrushed parts of the surface of the building material. The thickness of the coating is 1 mm. After curing at room temperature for 36 hours, the acid-resistant coating is obtained.

[0029] Example 2 10g silicon dioxide, 10g kaolin, 40g anhydrous calcium sulfate, 40g aluminum tripolyphosphate, 5g tantalum oxide, 5g yttria-stabilized zirconia, 5g boron oxide, 5g zinc oxide and 5g calcium carbonate are mixed, and ball-milled for 720min with alcohol and water as wet grinding liquids at a ball-milling rate of 100r / min. After taking out, dry for 48h, and pass through a 200-mesh sieve to obtain a solid phase powder. After mixing with 20g water glass in a beaker, 40g epoxy resin, 5g phthalic anhydride and 2g polydimethylsiloxane are slowly added, and stirring is continued until fully fused to obtain an acid-resistant coating material.

[0030] After cleaning the surface of building materials (such as steel structures, building walls and cement walls), Use a high-pressure air gun to blow away surface impurities. Connect the spray pot to the vacuum pump and evenly spray the acid-resistant coating material on the surface of the building material. The spray rate of the spray pot is 0.3 L / min, the spray distance between the spray pot and the metal is 80 cm, and the coating thickness is 0.5 mm. After curing at room temperature for 24 hours, the acid-resistant coating is obtained.

[0031] The spraying of the acid-resistant coating material is changed to brushing. The specific method is: use a brush to dip the acid-resistant coating and apply it on the surface of the building material. After brushing, use the brush again to repair the unbrushed parts of the surface of the building material. The thickness of the coating is 0.5 mm. After curing at room temperature for 24 hours, the acid-resistant coating is obtained.

[0032] Example 3 8g of silicon dioxide, 8g of kaolin, 30g of anhydrous calcium sulfate, 30g of aluminum tripolyphosphate, 1g of tantalum oxide, 1g yttria-stabilized zirconia, 1g boron oxide, 1g zinc oxide, and 1g calcium carbonate are mixed, and ball-milled for 60min with alcohol and water as wet grinding liquids at a ball-milling rate of 800r / min. After being taken out, they are dried for 36h, and passed through a 200-mesh sieve to obtain a solid phase powder. After mixing with 5g water glass in a beaker, 30g epoxy resin, 2g phthalic anhydride and 1g polydimethylsiloxane are slowly added, and stirring is continued until fully fused to obtain an acid-resistant coating material.

[0033] After cleaning the surface of building materials (such as steel structures, building walls and cement walls), Use a high-pressure air gun to blow away the impurities on the surface. Connect the spray pot to the vacuum pump and spray the acid-resistant coating material evenly on the surface of the building material. The spray rate of the spray pot is 6L / min, the spray distance between the spray pot and the metal is 10 cm, and the coating thickness is 10 mm. After curing at room temperature for 48 hours, the acid-resistant coating is obtained.

[0034] The spraying of the acid-resistant coating material is changed to brushing. The specific method is: use a brush to dip the acid-resistant coating material on the surface of the building material and apply it. After brushing, use the brush again to repair the unbrushed parts of the surface of the building material. The thickness of the coating is 10 mm. After curing at room temperature for 48 hours, the acid-resistant coating is obtained.

[0035] Example 4 5g silicon dioxide, 10g kaolin, 40g anhydrous calcium sulfate, 20g aluminum tripolyphosphate, 5g tantalum oxide, 1g yttria-stabilized zirconia, 3g boron oxide, 3g zinc oxide, and 3g calcium carbonate were mixed and ball-milled for 200min with alcohol and water as wet-milling liquid at a ball-milling rate of 600r / min. After being taken out, they were dried for 48h and passed through a 200-mesh sieve to obtain a solid phase powder. After being mixed with 15g water glass in a beaker, 20g of 0.1-20% polyvinyl alcohol was slowly added, and 40g of 0.1-20% polyvinyl alcohol was added. , A mixture of 5 g of 4-diaminodiphenylmethane and 1 g of 0.05-1% polyether defoamer is stirred continuously until fully blended to obtain an acid-resistant coating material.

[0036] After cleaning the surface of building materials (such as steel structures, building walls and cement walls), Use a high-pressure air gun to blow away surface impurities. Connect the spray pot to the vacuum pump and spray the acid-resistant coating material evenly on the surface of the building material. The spray rate of the spray pot is 2L / min, the spray distance between the spray pot and the metal is 30 cm, and the coating thickness is 5 mm. After curing at room temperature for 24 hours, the acid-resistant coating is obtained.

[0037] The spraying of acid-resistant coating material is changed to brushing. The specific method is: use a brush to dip the acid-resistant and fire-resistant coating on the surface of the building material and apply it. After brushing, use the brush again to repair the unbrushed parts of the surface of the building material. The thickness of the coating is 5 mm. After curing at room temperature for 24 hours, the acid-resistant coating is obtained.

[0038] Example 5 10g silicon dioxide, 5g kaolin, 40g anhydrous calcium sulfate, 30g aluminum tripolyphosphate, 1g tantalum oxide, 3g yttria-stabilized zirconia, 5g boron oxide, 1g zinc oxide, and 5g calcium carbonate are mixed, and ball-milled for 400min with alcohol and water as wet grinding liquids at a ball-milling rate of 400r / min. After being taken out, it is dried for 48h, and a solid phase powder is obtained after being sieved through a 200-mesh sieve. After being mixed with 10g water glass in a beaker, 30g phenolic resin, 2g 0.1~5% of a mixture of ethylenediamine and 1g polydimethylsiloxane are slowly added, and stirring is continued until fully fused to obtain an acid-resistant coating material.

[0039] After cleaning the surface of building materials (such as steel structures, building walls and cement walls), Use a high-pressure air gun to blow away surface impurities. Connect the spray pot to a vacuum pump and evenly spray the acid-resistant coating material on the surface of the building material. The spray rate of the spray pot is 5L / min, the spray distance between the spray pot and the metal is 50 cm, and the coating thickness is 8 mm. After curing at room temperature for 24 hours, the acid-resistant coating is obtained.

[0040] The spraying of the acid-resistant coating material is changed to brushing. The specific method is: use a brush to dip the acid-resistant coating material and apply it on the surface of the building material. After brushing, use the brush again to repair the unbrushed parts of the surface of the building material. The thickness of the coating is 8 mm. After curing at room temperature for 24 hours, the acid-resistant coating is obtained.

[0041] Comparative Example 1 5g of silicon dioxide, 5g of kaolin, 20g of aluminum tripolyphosphate, 3g of tantalum oxide, and 2g of yttrium oxide stabilized oxygen were added. Mix 2g zirconium dioxide, 2g boron oxide, 2g zinc oxide and 2g calcium carbonate, and ball mill for 360min with alcohol and water as wet grinding liquid, at a ball milling rate of 400r / min. Take out and dry for 48h, and pass through a 200-mesh sieve to obtain a solid phase powder. Mix it with 8g water glass in a beaker, and then slowly add a mixture of 30g epoxy resin, 8g phthalic anhydride and 1.5g polydimethylsiloxane, and continue stirring until fully fused to obtain an acid-resistant coating material.

[0042] Comparative Example 2 10g silicon dioxide, 10g kaolin, 40g anhydrous calcium sulfate, 40g aluminum tripolyphosphate, 5g tantalum oxide, 5g yttria-stabilized zirconia, 5g boron oxide, 5g zinc oxide and 5g calcium carbonate were mixed, and ball-milled for 720min with alcohol and water as wet grinding liquid at a ball-milling rate of 100r / min. After being taken out, the mixture was dried for 48h and passed through a 200-mesh sieve to obtain a solid phase powder. The solid powder was mixed with 20g water glass in a beaker to obtain an acid-resistant coating material.

[0043] After cleaning the surface of building materials (such as steel structures, building walls and cement walls), Use a high-pressure air gun to blow away surface impurities. Connect the spray pot to the vacuum pump and spray the anti-oxidation coating evenly on the surface of the building material. The spray rate of the spray pot is 0.3 L / min, the spray distance between the spray pot and the metal is 80 cm, and the coating thickness is 0.5 mm. After curing at room temperature for 24 hours, the acid-resistant coating is obtained.

[0044] Experimental Example 1 Acid resistance test Experimental method: The coatings prepared by the methods of Examples 1-5 and Comparative Examples 1-2 were sprayed on the surface of the steel plate sample with a spray thickness of 5 mm. After the coating was cured, the steel plate was immersed in a 65% nitric acid solution for 15 days and then weighed ( Figure 1 ).

[0045] Results: The steel plate samples sprayed with the coatings prepared in Examples 1-5 showed no discoloration or bubbling. However, after the samples sprayed with the coatings prepared in Comparative Examples 1 and 2 were placed in a 65% nitric acid solution for 3 days, the viscosity of the water glass disappeared, the coating turned into powder, and failed. Figure 2 As shown, the coating sprayed with the coating prepared in Example 1 was immersed in a 65% nitric acid solution for 15 days without any weight loss, discoloration, bubbling, etc. ( Figure 3 ), indicating that it can achieve long-term protection in an acidic environment.

Claims

1. An acid-resistant coating for construction, characterized in that: The method is composed of solid raw materials and liquid raw materials, wherein the solid raw materials are silicon dioxide, kaolin, anhydrous calcium sulfate, aluminum tripolyphosphate, tantalum oxide, yttria-stabilized zirconium oxide, boron oxide, and calcium carbonate; and the liquid raw materials are water glass, an adhesive, a curing agent, and a defoaming agent. The content of each raw material component is as follows: 5-20 parts of water glass, 5-10 parts of silicon dioxide, 5-10 parts of kaolin, 20-40 parts of anhydrous calcium sulfate, 20-40 parts of aluminum tripolyphosphate, 1-5 parts of tantalum oxide, 1-5 parts of yttria-stabilized zirconium oxide, 1-5 parts of boron oxide, 1-5 parts of zinc oxide, 1-5 parts of calcium carbonate, 20-40 parts of binder, 2-8 parts of curing agent, and 1-2 parts of defoaming agent.

2. The acid-resistant coating for construction according to claim 1, characterized in that: The modulus of the water glass is 2.6-3.7, and the particle sizes of the silicon dioxide, kaolin, anhydrous calcium sulfate, aluminum tripolyphosphate, tantalum oxide, yttria-stabilized zirconium oxide, boron oxide, zinc oxide, and calcium carbonate are 250-500 meshes.

3. The acid-resistant coating for construction according to claim 1, characterized in that: The adhesive is epoxy resin, phenolic resin and 0.1-20% polyvinyl alcohol.

4. The acid-resistant coating for construction according to claim 1, characterized in that: The curing agent is phthalic anhydride, 4 , 4-Diaminodiphenylmethane or 0.1~5% ethylenediamine.

5. The acid-resistant coating for construction according to claim 1, characterized in that: The defoamer is polydimethylsiloxane or 0.05-1% of a polyether defoamer.

6. The method for preparing the acid-resistant coating for construction according to claim 1, characterized in that: The specific method is: mix the solid raw materials in proportion, use alcohol and water as wet grinding liquid for ball milling for 60-720 minutes, the ball milling rate is 100-800r / min, take out and dry for 36-48 hours, pass through a 200-mesh sieve to obtain solid powder, mix it with water glass in a beaker, and then slowly add the mixture of adhesive, curing agent and defoaming agent and obtain the acid-resistant coating paint for construction through magnetic stirring.

7. The method for preparing the acid-resistant coating for construction according to claim 6, characterized in that: The magnetic stirring time is 20~400min, and the stirring speed is 100~700r / min.

8. The use of the acid-resistant coating material for construction according to claim 1 in preparing a coating on a building surface, characterized in that: The coating method is to grind and clean the surface of the building material, and then evenly apply it on the surface of the building material by spraying or brushing, with a coating thickness of 0.5~10mm.

9. The use according to claim 9, characterized in that: Spraying mainly involves connecting a spray pot to an air compressor and relying on strong air pressure to spray the coating onto the steel substrate. The spraying rate of the spray pot is 0.3~6L / min, and the spraying distance from the metal is 10cm~80cm.

10. The use according to claim 9, characterized in that: The building surface material is steel structural parts, building walls or cement walls.

Citation Information

Patent Citations

  • Alkali-resistant fireproof coating for building as well as preparation method and application of alkali-resistant fireproof coating

    CN118027717A

  • High-strength bolt and production process thereof

    CN118532383A

  • High-temperature-resisting coating and its production

    CN1896149A

  • Strain tolerant corrosion protecting coating and spray method of application

    US20070141369A1